GAMBARAN TINGKAT PENGETAHUAN DAN KEPATUHAN PERAWAT MENGGUNAKAN HANDSCOON DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH WANGAYA - Lastari, Ni Wayan Uni; Krisnawati, Komang Menik Sri; Puspita, Luh Mira (Coping: Community of Publishing in Nursing; Vol 9 No 2 (2021): April 2021DO - 10.24843/coping.2021.v09.i02.p06, 2021)
Nosocomial infections are infections that are obtained in health services that can spread through patients, health workers, and visitors. The effort to protect nurses and patients from nosocomial infections is the application of standards precaution. Important standards precaution that are adhered to by nurses are the use of personal protective equipment (PPE) such as the use of handscoons. The research aimed to determine the level of knowledge and compliance of nurses using handscoons in the Inpatient Room of Wangaya Hospital. This study was a descriptive research. The sample in this study were 44 nurses who were selected by total sampling technique. The instruments that used in this study were questionnaires and observation sheets using references from the pyramid using the handscoon according to WHO. The level of knowledge of nurses' knowledge and compliance using handscoons was analyzed using frequency distribution. The results showed that 65.1% responden have enough knowledge, 34.9% have good knowledge, while 44.2% of respondents have enough unity, 55.8% of respondents have good compliance. Based on the results of the study, it is recommended to maintain and further enhance the knowledge and compliance of using handscoon by following the socialization about the use of handscoon.